2012
DOI: 10.9798/kosham.2012.12.5.135
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study on the Designation of a Special Disaster Area by Considering the Climate Extreme Value

Abstract: Due to natural disasters, the central government generally extends support for the local authorities faced with disaster recovery and the loss of public and private damages. Also, the current methodology for designation of an area as a special disaster zone has limitations in the distinguishing a regions from one another according to disaster intensity factors and physical damages in the zones. This study addresses the damage estimation in a region by using the annual extreme values of daily precipitation whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The Korean Government implemented a special disaster region declaration program to effectively restore large-scale damages caused by long-term flooding of over 10 days in parts of the Gyeongnam region due to heavy rainfall from August 4 to August 11 in 2002. [1] When examining the special disaster region declaration status up until now, it was found that damage due to Typhoon 'Ewiniar' and heavy rainfall from July 9 to 29, 2006 was the longest. During this period, basic social facilities were unable to execute their roles.…”
Section: A Purpose Of Studymentioning
confidence: 99%
“…The Korean Government implemented a special disaster region declaration program to effectively restore large-scale damages caused by long-term flooding of over 10 days in parts of the Gyeongnam region due to heavy rainfall from August 4 to August 11 in 2002. [1] When examining the special disaster region declaration status up until now, it was found that damage due to Typhoon 'Ewiniar' and heavy rainfall from July 9 to 29, 2006 was the longest. During this period, basic social facilities were unable to execute their roles.…”
Section: A Purpose Of Studymentioning
confidence: 99%
“…The Korean Government introduced the special disaster area declaration policy to effectively address and restore heavy damages from a prolonged flooding (more than 10 days) by torrential downpours in a Gyeongnam area, during August 4-11, 2002 [1]. Among the special disaster areas declared until now, no.…”
Section: A Purpose Of Studymentioning
confidence: 99%